67. SARS-CoV-2 Transmission: Preliminary Findings from a Household-based Study. (31st December 2020) - Grijalva, Carlos G; Zhu, Yuwei; Halasa, Natasha B; Kim, Ahra; Rolfes, Melissa A; Steffens, Andrea; Reed, Carrie; Talbot, Helen
Abstract: Background: Social distancing measures, such as shelter-in-place or stay-at-home orders, are recommended for control of community transmission of SARS-CoV-2. Few studies, however, have characterized the transmission of SARS-CoV-2 infections in households. Methods: We conducted a case-ascertained study of household transmission in Nashville, TN starting in April 2020, after recommendations to stay at home were enacted. Index cases were ambulatory patients identified through clinical RT-PCR testing at Vanderbilt walk-in-clinics dispersed across the Nashville metropolitan area. For this study, the index case was the first person presenting with respiratory or compatible symptoms in a household and who lived with at least one other household member. After informed consent was obtained, household members were remotely trained in the self-collection of nasal swabs and use of REDCap electronic questionnaires. Household members completed daily symptom diaries and collected daily nasal swabs for 14 days. Contact patterns within households before and after disease onset were ascertained. Nasal swab samples were tested using RT-PCR at an academic research laboratory. Results: At the time of writing, 18 families were enrolled (including 18 index cases and 34 household members) with at least 1 follow-up nasal swab tested. The median age of index cases and household members was 37 years (IQR: 26–46) and 27 years (15–39), respectively. The median number of days from index patient onset of symptoms to first sample collected in the household was 4 (2–5). Before onset of symptoms, 83% of index cases spent >4 hours in the same room with at least one other household member, whereas after disease onset and diagnosis, 44% did. Among 34 non-index household members, 18 (53%) had a positive test during follow-up; the median number of days from index case's symptoms onset to first positive detection in a household member was 4.5 (3–5) days. Interestingly, 13 (72%) of 18 secondary infections were detected within the first 3 days of follow-up, whereas 5 (28%) were detected during subsequent days. Conclusion: These observations suggest that transmission of SARS-CoV-2 within households is high, with many infections detected during the initial days of study follow-up. Disclosures: Carlos G. Grijalva, MD, MPH, AHRQ (Grant/Research Support)Campbell Alliance (Grant/Research Support)CDC (Grant/Research Support)FDA (Grant/Research Support)Merck (Consultant)NIH (Scientific Research Study Investigator)Pfizer (Consultant)Sanofi (Consultant)Sanofi (Grant/Research Support) Natasha B. Halasa, MD, MPH, Genentech (Other Financial or Material Support, I receive an honorarium for lectures - it's a education grant, supported by genetech)Karius (Consultant)Moderna (Consultant)Quidel (Grant/Research Support, Research Grant or Support)Sanofi (Grant/Research Support, Research Grant or Support)